Grumpy monkey spring fever - Lang, Suzanne; Lang, Max, 1982- (New York : Random House Studio, 2024)
When Jim Panzee wakes up feeling silly, Norman playfully suggests Jim has spring fever, sparking excitement and chaos among Jim and their animal friends until Norman clarifies the true meaning of spring fever
003-007.
Grades K-1.
Keywords: Mood (Psychology) -- Juvenile fiction; Spring -- Juvenile fiction; Chimpanzees -- Juvenile fiction; Animals -- Juvenile fiction; Mood -- Fiction; Spring -- Fiction; Chimpanzees -- Fiction; Animals -- Fiction; Spring -- Juvenile fiction; Chimpanzees -- Juvenile fiction; Animals -- Juvenile fiction; picture books; Animal fiction; Humorous fiction; Picture books